A New Bubble Pick-Up Technique as a Rapid Flotation Test Method - A. F. Lee (The Southern African Institute of Mining and Metallurgy, 1969)
Dr E. C. Hanekom (Visitor): Two years ago we used the bubble pick-up technique as developed at Anglo American Corporation for screening candidate flotation agents prepared in our laboratories. It was obviously necessary to know to what extent the technique gave reproducible results and a statistical evaluation of the test method was made using a mineral sample provided by Anglo American Corporation. A bubble of 2.0 mm diameter was used and the measuring graticule was divided into squares (units) with sides of 5.0 mm at 25 X magnification. The mineral granules had diameters from 53 to 74 mm. The bubble was loaded by depressing it against a layer of mineral grains to give an arbitrary but constant compression of 0.4-0.5 mm. It was rolled five times through 2 mm horizontal displacement. The bubble was then lifted, its load compacted by gently stirring and the projected area measured in squares (units) on the grid. Each substance was tested at 5 ppm concentration in distilled water at five points in the pH range 3-6. With these standardized conditions of operation the reproducibility of the test was studied. Four materials were tested and at each pH value the procedure of forming a bubble, picking up granules and counting the units was repeated ten times. From these results the standard deviation for a single count at any pH value was calculated for each material (Table 1. The coefficient of variation of approximately 3 per cent was relatively low and it was decided that further refinements in the counting procedure would be of doubtful benefit with the present apparatus. Similar experiments were carried out with 12 sample materials. In this case the bubble formation and pick-up were repeated four times at each pH value, the mean value was calculated for each set of four observations and final pick-up values for the materials were obtained by selecting the highest mean count. Each test was completely repeated a number of times as indicated in Table 2 and the standard deviation calculated. The results allowed the selection of the more promising materials and the rejection of poor performers at the 95 per cent confidence level. All tests were carried out by one operator. Some evidence was obtained that the method is sensitive to operator bias. In conclusion it can be said that from all the results analyzed it would appear that once operation conditions are fixed (viz operator, pH control) the precision of the method is adequate. The author wishes to thank Messrs African Explosives and Chemical Industries Limited for permission to publish these data. G. S. Stander and C. J. Kooij (Visitors): We must congratulate Mr Lee for this most interesting and useful development of the pick-up experimental method. It certainly provides research workers with an instrument which makes flotation more of a science and less of an art. We visited Mr Lee at his laboratory where he gave us a demonstration of the bubble pick-up instrument and technique as developed and improved by him.